Formación de nódulos en estacas recién establecidas de Gliricidia sepium (Fabaceae) en tres suelos de Ciudad Colón, Costa Rica - Di Stéfano, José F (Universidad de Costa Rica, 1997)
Nodule fonnation was studied for 3.5 years in recently established Gliricidia sepium cuttings (5-7 cm diam. 180-190 cm long) planted on three soil types. They were compared with 20 year-old trees on a coffee plantation. After the second year, samples (n=3) were obtained periodically at I m from the cutting and 20 cm deep on each of the soil types. No nodules were observed on the first year. On the third year, the highest production occurred during the flrst rainy period and on Inceptisols (301cutting/475.2 cm3, SO=I4.4 on June), while the poorest took place during the dry season and on Ultisols. These data were correlated with foliar flushing, precipitation and soil hurnidity. The amount of nodules was similar to those of the older trees after the third year, but the N-rich fertilizer applied to the coffee plantation delayed the process